Japanese legends and folklore samurai tales, ghost stories, legends, fairy tales, myths and historical accounts - Redesdale, Algernon Bertram Freeman-Mitford Baron 1837-1916.; Foster, Michael Dylan 1965- (Tokyo Rutland, Vermont Tuttle Publishing, 2019)
"Japanese Legends and Folklore invites English speakers into the intriguing world of Japanese folktales, ghost stories and historical eyewitness accounts. With a fascinating selection of stories about Japanese culture and history, A.B. Mitford--who lived and worked in Japan as a British diplomat--presents a broad cross section of tales from many Japanese sources. Discover more about practically every aspect of Japanese life--from myths and legends to society and religion."--Amazon.com.
Contents in English and Japanese.
Includes bibliographical references.
Keywords: Folklore -- Japan; Japan -- Social life and customs